A Study on The Capabilities of Cellulolytic Bacteria in Degrading Feed Fiber - Utami, Rosdiana; Syamsuhaidi, Syamsuhaidi; Kisworo, Djoko; Depamede, Sulaiman Ngongu; Ketut Gde, Wiryawan; Bulkaini, Bulkaini (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The utilization of local feedstuffs is a cost-effective strategy to reduce production expenses in animal husbandry. Enhancing the nutritional quality of these feedstuffs through fermentation presents a viable approach. This study investigates the efficacy of cellulolytic bacteria in degrading fiber in three local feed materials: duckweed (Lemna minor), water hyacinth (Eichornia crassipes), and lamtoro (Leucaena leucocephala). We employed a completely randomized block design with feed types as the block and levels of starter culture as treatment. Pediococcus pentosaceus, identified for its cellulase enzyme production with a clear zone of 4 cm on starch media, was utilized as the starter culture. The experimental procedure involved spraying Pediococcus pentosaceus onto duckweed, water hyacinth, and lamtoro, followed by incubation. The results indicated that Pediococcus pentosaceus effectively produced cellulolytic enzymes and significantly reduced crude fiber in duckweed by 18.18%, in water hyacinth by 9.17%, and in lamtoro by 4.23% (p < 0.05). Additionally, the crude protein content increased in all samples: by 4.69% in duckweed, 2.71% in water hyacinth, and 2.13% in lamtoro (p < 0.05). Among the treatments, the optimal outcome was achieved with 3 ml of Pediococcus pentosaceus. This study demonstrates the potential of Pediococcus pentosaceus for improving the nutritional profile of local feedstuffs through fermentation.